Value Relevance of General Government National Accounts with ESA2010 Accrual Accounting Framework. Association of ESA2010 Reporting Quality with Decision Making and Accounting Standardization - Michalis Bekiaris; Antonia Markogiannopoulou (Journal of Accounting and Management Information Systems (JAMIS), 2022)
Purpose - The necessity for a reliable set of international standards for the compilation of national accounts introduced the accrual accounting framework of the European System of Accounts (ESA 2010). Extensive efforts are made for convergence between Government Accounts (GA) and National Accounts (NA) under accounting standards. Design/methodology/approach - This study investigated the quality of governmental NA, in the context of ESA 2010, from 1999 through 2019, using relative value relevance models of long-term government bond yields. Findings - i) The accrual accounting framework ESA2010 generates value relevant (thus qualitative) NA financial reporting in EU member states and the United Kingdom (UK); ii) The financial variables that better interpret bonds' return, thus governments' necessity to borrow money, are showcased; iii) The usefulness of the ESA2010 conceptual framework for decision and policy making process considering that the accrual accounting basis fosters the financial reporting quality, is demonstrated; iv) The quality results set the premise for further discussion for the harmonization and alignment process of accounting standardisation with the ESA2010 accrual accounting framework as a resource for policy and decision making. Limitations - The methodology of value relevance models that is employed to assess the governmental statistical reporting quality with the ESA2010 accrual accounting framework is a private sector technique. Originality - This study contributes theoretically as it fosters the quality of accrual accounting basis. It moreover provides an empirical and practical contribution by introducing relative value relevance econometric models that provide stakeholders with reliable information on the financial position and performance of the government. It showcases significant financial variables and coefficients of statistical reporting for each government. With its value relevant results, it supports evidence-based decision making, allows comparisons between EU governments and the UK, and contributes to increased transparency and accountability.
Keywords: H83; M41; 650; IPSAS; EPSAS; ESA2010; national accounts; value relevance; bond return